ACTIVITIES OF BUKHARA STATE PEDAGOGICAL AND TEACHERS` INSTITUTE DURING WORLD WAR II (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, you will see that achievements and shortcomings in education and science in Uzbekistan during World War II were highlighted on the example of the Bukhara State Pedagogical and Teacher's Institute. At the same time that the war began, all processes in the institute are re-structured or modified, depending on the demand for war. The institute also described the preparation of units made up of volunteer students for the front, the sending of material and military assistance for the front, as well as many noble works carried out by institute pedagogical workers. You can also get information about how the problems that arose in the conditions of war were eliminated, about the research work carried out.